Heterosis and combining ability studies in Sesame: Heterosis and combining ability studies in Sesame - P M MISTRY; P N ZALA; P K JAGTAP (Journal of Oilseeds Research, 2023)
The present investigation on heterosis and combining ability using line × tester analysis at NRS, NAU, Vanarasi Gujarat indicated that there is sufficient amount of variation present in the tested material for seed yield and its components. Non-additive genetic variances were important in the inheritance of all the traits. The preponderance of non-additive genetic variance was observed in the inheritance of days to 50 % flowering, days to maturity, plant height, effective branches/plant, capsules/plant, capsule length, seeds/capsule, 1000-seed weight, harvest index, seed yield/plant and oil content which suggested that heterosis breeding would be more suitable for the improvement of these traits in sesame. Further the crosses which exhibited high seed and oil yield along with high heterosis and heterobeltiosis should be exploited through pedigree method to obtain desirable transgressive segregants with high seed yield along with high oil content.